Effects of xylazine and dexmedetomidine on equine articular chondrocytes in vitro. (March 2017) - Mancini, Francesco; Nannarone, Sara; Buratta, Sandra; Ferrara, Giuseppina; Stabile, Anna Maria; Vuerich, Matteo; Santinelli, Isabella; Pistilli, Alessandra; Chiaradia, Elisabetta
Abstract: Objective: To assess the effects of xylazine and dexmedetomidine on equine chondrocytes, in vitro . Study design: Prospective, experimental study. Study material: Equine articular chondrocytes from five male horses. Methods: Chondrocytes were isolated from healthy equine articular cartilage of the metacarpo/metatarsophalangeal joints. Cell viability was assessed using the WST-8 assay by exposing chondrocytes to xylazine (0.5, 1, 2, 4, 8, 16.6, 25, 50 mg mL −1 ) or dexmedetomidine (0.001, 0.005, 0.01, 0.05, 0.175, 0.25 mg mL −1 ) for 15, 30 and 60 minutes. Based on the results of these tests, cells were treated with xylazine (1, 4, 25 mg mL −1 ) or dexmedetomidine (0.05, 0.175, 0.25 mg mL −1 ) for 15 minutes to further evaluate: cell viability by neutral red uptake; cell membrane integrity by lactate dehydrogenase release and by fluorescence microscopy with Hoechst 33342 and propidium iodide (PI), and apoptosis by flow cytometry using double staining with annexin V-fluorescein isothiocyanate/PI and by cell morphology. Results: Both drugs reduced cell viability in a dose-dependent manner. Specifically, all xylazine concentrations, except 0.5 mg mL −1 and 1 mg mL −1, significantly reduced cell viability, whereas the effects of dexmedetomidine were evident only at 0.175 mg mL −1 and 0.25 mg mL −1 . The highest concentrations of xylazine (25 mg mL −1 ) and dexmedetomidine (0.25 mg mL −1 ) caused loss of membrane integrity. Cell morphology and flow cytometry analyses demonstrated signs of late apoptosis in xylazine-treated cells, and signs of late apoptosis and necrosis in dexmedetomidine-treated cells. Conclusions and clinical relevance: This study offers new insights into the potential chondrotoxicity induced by dexmedetomidine and xylazine. Therefore, the intra-articular administration of α2 -agonists should be conducted with care, especially for doses of ≥ 4 mg mL −1 of xylazine and 0.175 mg mL −1 and 0.25 mg mL −1 of dexmedetomidine.